Теоретичні засади фінансово-економічного стимулювання розвитку смарт-промисловості - Zaloznova, Yuliya S.; Chekina, Viktoriia D. (Institute of Industrial Economics of NAS of Ukraine, 2023)
The article examines the research of scientists on the development of a new industrial policy and analyzes papers devoted to assessing financial and economic incentives for the development of new technologies, innovations, smart industry and Industry 4.0.The intervention of state industrial policy in cases where the market fails to allocate resources effectively is analyzed, and the relevance of industrial policy is substantiated by economists and political leaders of the leading countries of the world.The theoretical foundations of the state innovation policy are defined, which is the link between the policy of scientific and technological progress and industrial policy aimed at developing principles for supporting the bringing of ideas and innovations to the market.It has been established that the widely used traditional instruments of innovation policy are government support for research organizations, primarily state universities and scientific institutes. Other common tools for financial and economic stimulation of industry are competitive funding of research (both fundamental and applied), fiscal preferences (tax incentives and subsidies) for R&D by industrial enterprises, and government support for technology transfer.Foreign studies of the theoretical aspects of financial and economic stimulation of development are systematized and grouped into the following areas: justification of state support for research organizations and competitive financing of scientific projects, assessment of the effectiveness of the use of fiscal preferences for R&D, analysis of the impact of state support in the process of technology transfer for the development of smart industry and stimulating the development and commercialization of innovations (patent box mode).An example is given of one of the areas of modern research into financial support for stimulating a particular industry – fiscal preferences for the production and sales of electric vehicles and charging stations.It has been established that financial and economic incentives for the development of new technologies and their implementation in the smart industry have a positive impact on the development of start-ups, innovation activities, the development of new products, an increase in the number of patents, additional output volumes, growth in investment and employment.It would be advisable to focus further research on analyzing the experience of foreign countries in stimulating the development of smart industry with the help of financial instruments (including fiscal instruments).